Artificial Intelligence Application for Unmanned Aerial Vehicle Navigation (Моделювання, керування та інформаційні технології, 2023)
This paper analyzes the use of artificial intelligence technology for autonomous control of an unmanned aerial vehicle. The remote control in difficult conditions limits the capabilities of the unmanned aerial vehicle and reduces the efficiency of the entire system. Therefore, an urgent task is the autonomous navigation of an unmanned aerial vehicle using artificial intelligence technology. In this case, the aircraft can perform tasks depending on the variability of external factors. Artificial intelligence in the autonomous control of an unmanned aerial vehicle plays an important role in ensuring the characteristics of human control. The paper explores several artificial intelligence approaches for autonomous navigation of an unmanned aerial vehicle: mathematical optimization, learning programs. Various characteristics, types, models of navigation are analyzed. The equation for the errors of the inertial navigation system in the normal earth’s coordinate system is analyzed.Keywords— Unmanned Aerial Vehicle; autonomous navigation; artificial intelligence; navigation models.